The sexually selected ejaculate - Hopkins, B (2018)
The ejaculate is composed of many different parts: proteins, lipids, and much else travels alongside sperm. With so many elements comes the problem of composition. Does the mix matter for male reproductive success? To what extent is the composition fixed? What happens when males lose control over the composition? It is with these questions that this thesis is principally concerned. I start by testing whether males alter ejaculate composition in relation to the intensity of male-male competition. I find that divergent allocation rules govern the transfer of sperm and seminal fluid proteins (‘SFPs’). While the allocation of both responds to competition, only SFP allocation responds to its intensity. I further show that variation between SFPs in their responsiveness leads to differentially-composed seminal fluid. The resulting ejaculate compositions are each accompanied by distinct costs and benefits for male reproductive performance, some of which appear specific to seminal fluid. I next demonstrate that loss of BMP-regulated secretions from a seminal fluid-contributing cell-type (‘secondary cells’) imparts a syndrome of dysregulation on male and female reproductive performance. Within this, males lose the ability to reduce female receptivity to remating, but gain an advantage in defensive sperm competition. Through a systematic dissection of different episodes influencing sperm competition outcome, I find that loss of these secretions influences sperm entry into storage and potentially enhances their resistance to displacement. In the following two chapters I show that loss of BMP-regulated secondary cell secretions and the keystone SFP sex peptide affects seminal fluid transfer to females. In both cases, I find clear signals of between-SFP dependencies in the regulation of SFP transfer, which collectively highlight novel mechanisms of seminal fluid organisation. I argue that these organising mechanisms may be used to a male’s advantage to exercise fine-scale, real-time control over the transfer of ready-made seminal fluid.